Pengaruh Kegiatan Seni Finger Painting dalam Melatih Kemampuan Lobus Oksipital Anak Terhadap Pengenalan Warna Usia 4-5 Tahun - Insani, Putri; Aulevpia, Okta; Vironica, Wince (Yayasan Darussalam Bengkulu, 2024)
The occipital lobe is located posterior to the parietal lobe and above the parieto-occipital fusura which separates it from the cerebrum. Anatomically, area 17 is the primary visual cortex, the medial surface of the occipital lobe along the superior and inferior parts of the calcanius sulcus. And areas 18, 19 are visual associations, located parallel to area 17 which extends to the lateral surface of the occipital lobe. Recognizing colors is one of the scientific indicators which is included in function of the occipital lobe. Playing finger painting is fun for most children. Children aged four to six years are interested in expressing whatever they see in the form of images, colors or the results are still in the form of simple scribbles. Through finger painting activities, it is a painting technique using fingers or the palm of the hand on paper or a board.